Incentive Pay Plan for Improving Safety Performance of Seaport Employees - MD. Rayhanul Kabir; Wei Liu (International Journal of Engineering and Management Research, 2023)
Safety is a proactive, continuous, systemic, and comprehensive process which focuses on reducing risk, injuries, and fatalities in work. Seaports have still higher rate of injuries and therefore innovative initiatives to reduce accidents and improving safety conditions are needed at seaports. Chittagong Seaport is one of the busiest seaports in the world. Due to the complexity and forceful nature of work, management of health and safety may not continuously be up-front in CPA. This study focuses on the health and safety aspects of the Chittagong seaport labor system. In this paper, the incentive as an approach to motivate port employees in using safety equipment was assessed. After applying this method in Chittagong Seaport, there is a behavioral change among the employees. It has been found from the result that there is a significant relationship between incentive and safety performance. The result of this study showed that how incentive has a positive impact in enhancing safety performance of port employees. The use of incentives can be helpful for seaport’s labors to be associated with safety programs.